2018
DOI: 10.5604/01.3001.0012.2079
|View full text |Cite
|
Sign up to set email alerts
|

Wpływ kompetencji przedsiębiorczych naukowców na współpracę nauki i biznesu

Abstract: Współpraca nauki i biznesu nabiera w obecnych czasach coraz większego znaczenia. Zmieniająca się rola szkoły wyższej powoduje konieczność nawiązywania współpracy z otoczeniem gospodarczym, w tym w zakresie komercjalizacji wyników badań naukowych. Problematyka prezentowanego artykułu dotyczy kompetencji przedsiębiorczych naukowców, rozpatrywanych w kontekście współpracy między szkołą wyższą a przedsiębiorcami. Celem przeprowadzonego badania była próba identyfikacji kompetencji naukowców, które determinują podję… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Changes in education programs not only affect students but also the faculty, as a shift in the teaching paradigm is the basis for developing the entrepreneurial competences of its lecturers via interactive workshops and hands-on exercises [33]. Many HEIs foster their own entrepreneurial ecosystems by re-mastering their study programs and conducting projects that include students, academic staff and business representatives [34][35][36][37][38][39]. The ecosystem drivers are "teacherpreneurs", who blend risk-taking and entrepreneurial leadership with the culture of creativity and reflection [40], as well as university-based ventures that are the basis for students' business plan contests and their implementation [41].…”
Section: Introductionmentioning
confidence: 99%
“…Changes in education programs not only affect students but also the faculty, as a shift in the teaching paradigm is the basis for developing the entrepreneurial competences of its lecturers via interactive workshops and hands-on exercises [33]. Many HEIs foster their own entrepreneurial ecosystems by re-mastering their study programs and conducting projects that include students, academic staff and business representatives [34][35][36][37][38][39]. The ecosystem drivers are "teacherpreneurs", who blend risk-taking and entrepreneurial leadership with the culture of creativity and reflection [40], as well as university-based ventures that are the basis for students' business plan contests and their implementation [41].…”
Section: Introductionmentioning
confidence: 99%
“…These are competences that can be called entrepreneurial skills of scientists, helping in establishing and maintaining implementation with business. In the results of earlier studies, this type of skills was indicated as an indispensable element of the entrepreneurial competence model of researchers (Jakubiak and Chrapowicki, 2018).…”
Section: Discussionmentioning
confidence: 95%
“…Along with the changing role of higher education institutions, their openness to the environment and flexibility, the expectations regarding the competences of academic staff are also changing (Osiri and McCarty, 2013). They are expected to be involved not only in the implementation of scientific research and teaching, but also to have competences enabling them to establish and maintain lasting relationships with stakeholders, entrepreneurs included (Jakubiak and Chrapowicki, 2018).…”
Section: Business-science Cooperation In the Literaturementioning
confidence: 99%
“…Naukowcy wymianiają jako główne determiananty możliwość praktycznego zastosowania wyników badań naukowych i ich realnego wykorzystania (komercjalizacji), perspektywę interdyscyplinarnej współpracy oraz korzyści finansowe. Podobne czynniki wskazywali respondenci w prowadzonych wcześniej badaniach w branży technologicznej (Jakubiak, Chrapowicki, 2018). Można więc przypuszczać, że podobne determinanty cechują chęć wspólpracy naukowców z przedsiębiorcami, niezależnie od reprezentowanej branży.…”
Section: Wnioski Z Badań I Dyskusjaunclassified